Occupational stress among educational counselors. (Journal of the College of Basic Education, 2022)
The current research aims to identify the occupational stress of educational counselors, and for the purpose of achieving the goal of the research, the researchers used the descriptive approach, and the researchers prepared the occupational stress scale, and for the purpose of conducting the statistical analysis of the occupational stress scale, a sample consisting of (400) men and women were selected and the sample was chosen randomly from guides The educators in the directorates of education and the researchers extracted the psychometric characteristics of the scale and the use of statistical indicators, and the research reached a number of results, including the involvement of educational counselors in lectures, seminars and training programs that help them withstand professional stress during their extension work, and in light of the findings of the research results, the researchers recommended a group of recommendations and suggestions